2021
DOI: 10.1371/journal.pone.0257046
|View full text |Cite
|
Sign up to set email alerts
|

Does school reopening affect SARS-CoV-2 seroprevalence among school-age children in Milan?

Abstract: The benefits of schools’ closure, used as a containment strategy by many European countries, must be carefully considered against the adverse effects of child wellbeing. In this study, we assessed SARS-CoV-2 seroprevalence, which better estimates the real extent of the infection unraveling asymptomatic cases, among schoolchildren aged 3 to 18 in Milan, using dried blood spot, a safe and extremely viable methods for children, and then compared it between September 2020 and January 2021. Secondly, we evaluated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 9 publications
2
8
0
Order By: Relevance
“…Low attack rates within schools were also reported from a large study from North Carolina, USA, which included over 100,000 staff and students from 13 school districts [9]. An Italian study did not find any increase in infection incidence among students who attended in-person classes compared with those who attended remote learning [8]. On the other hand, breakdown in infection control practices, e.g.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Low attack rates within schools were also reported from a large study from North Carolina, USA, which included over 100,000 staff and students from 13 school districts [9]. An Italian study did not find any increase in infection incidence among students who attended in-person classes compared with those who attended remote learning [8]. On the other hand, breakdown in infection control practices, e.g.…”
Section: Discussionmentioning
confidence: 75%
“…While overall evidence suggests little transmission within schools, controversy still exists regarding the role of schools and in-person attendance with spread of infection. Seroprevalence studies over time have suggested low levels on within-school transmission, with majority of the infections acquired outside the school settings [8]. Within the schools, in-person sporting activities have been associated with a higher risk of transmission [9].…”
Section: Introductionmentioning
confidence: 99%
“…29 A study in Italy also found antibody rates rise in teachers over the school year but concluded that school opening did not “amplify transmission”. 48 Attack rates involving staff and students in schools are highly variable across studies, but a recent meta-analysis of five contact-tracing studies found a 10-fold lower attack rate (0.7% of contacts becoming infected) in schools than households (7.6%). 49 …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, age was later not identified as a variable independently associated with SARS-CoV-2 seropositivity. There are few studies where higher seropositivity in younger age is described [ 15 , 30 , 31 ]. On the contrary, a lower seroprevalence is often reported in younger children [ 9 , 24 , 26 , 32 ].…”
Section: Discussionmentioning
confidence: 99%